COMPARATIVE STYLISTIC ANALYSIS OF SELECTED BAETA'S RINCONADA POEM AND ITS ENGLISH TRANSLATION - Fajardo, Dan Fereth; Oliveros, Nemuel; Ibarbia, Julia Ledah; Derecho, Desiree; Pesebre, Rhea (Journal of English Education and Linguistics, 2023)
This study applies a stylistic analysis, building on the paradigm established by Latif, Ajmal, and Maqbool (2022), to examine Elbert Baeta's Rinconada poem "Sawa Sa Poste Otsenta'y Seis'' and Kara Santos' English translation. The study, which focuses on the phonological and semantic levels of language, investigates how these poets use linguistic features to express meaning and aesthetic appeal. The phonological level focuses on alliteration, consonance, and assonance, unraveling the complicated web of sounds that give life to the lines. At the same time, the semantic level weaves a complex tapestry of meaning through metaphor, symbolism, and imagery. The study, moreover, used a comparative approach in qualitative research to identify similarities and differences between the original Rinconada poem and its English translation. The findings shed light on the dynamic interplay between linguistic choices and poetic meaning, allowing us to gain a better grasp of the artistry present in these culturally complex verses.